Identification of the behavior of students and parents regarding the family to maintain oral health - Ortiz Fernández, Lita (2009)
The aim of this study was to determine the behavior of students, parents and teachers inmaintaining the oral health of children. Quasi-experimental research, cualicuantitativo was conducted in a sample of 46 children aged 6 years old, which evaluated oral health status of the initial and final (initial and manifest caries) was measured by the plaque index also was determined knowledge and meanings in oral health of the parents or mothers, both teachers. Implemented a training model for enhancing knowledge and reconceptualization of knowledge in oral health, with scenarios in participatory learning teachers and parents also will perform preventive care to children with emphasis on permanent teeth. The results showed differences before and after training. Manifest caries showed significant changes (p-value) 0.0 after training and preventive care of 61 %, became manifest caries treated by 54% and 7% untreated caries says. The percentage of children with fillings at the beginning of the intervention was 4.3%, after training and preventive care in the manifest caries roce to 58.6% showed significant changes (p-value) 0.0, the number first molars with sealants was significantly protected (p-value) 0.00, an initial 0% to 95.6%, the index of oral hygiene before and after training found significance (p-value) 0.0; children plaque increased from 0% to 6.5%, children with poor hygiene grade 3, they moved to take up a regular hygiene 84.8%. In terms of training in oral health of parents and mothers after the intervention was found statisticafly significant differences (p-value) 0000. We conclude that access to oral health of children at early ages, depends on collective cultural barriers in both the family and at school. Access to basic services with a preventive approach promotes a participatory promotional change of attitude of child and its environment.